The impact of green marketing strategy on the firm's performance in Malaysia - Hasan, Zuhairah; Ali, Noor Azman (Elsevier, 2015)
This is a conceptual paper to study the impacts of green marketing strategy on the Malaysian certified ISO 14001 Environmental Management System firms’ performance. The paper aims at presenting the reviews of the literature on the green marketing and analyses the two factors that will influence the firms’ performance. Despite the rising trend of consumers that willing to spend for a green product and the potential of green product, previous literature revealed that green marketing has encountered some challenges. The conclusion that was drawn is that, green innovation and the green promotion have a positive effect on the firms’ performance.